Serogroup B meningococcal vaccines-an unfinished story. - Sadarangani, M; Pollard, A (2010)
Most invasive meningococcal disease in developed countries is caused by Neisseria meningitidis with a serogroup B capsule. However, despite availability of vaccines for other serogroups since the 1960s, no serogroup B vaccine exists. In this Review we look at the development of serogroup B vaccines over the past 40 years. Outer membrane vesicle vaccines have been successfully used to control geographically isolated epidemics, but most have not been highly immunogenic in young children or provided broad cross-protection from infections with other strains. Vaccines based on subcapsular antigens have recently produced promising results in early clinical trials, and the disease burden might be substantially reduced over the next few years.